Beyond nudge advancing the state-of-the-art of behavioural public policy and administration - Ewert, Benjamin; Loer, Kathrin 1980-; Thomann, Eva 1981- (Policy Press, 2024)
First published as a special issue of Policy & Politics journal, this book situates reforms known as 'nudges' or 'behavioural interventions' which have emerged in public policy and administration within a broader tradition of methodological individualism.
Title from publisher's bibliographic system (viewed on 28 Mar 2024)
1. Beyond nudge: advancing the state-of-the-art of Behavioural Public Policy and Administration - Benjamin Ewert, Kathrin Loer and Eva -- n -- 2. Advancing behavioural public policies: in pursuit of a more comprehensive concept - Benjamin Ewert and Kathrin Loer -- 3. A behavioural model of heuristics and biases in frontline policy implementation - Alice Moseley and Eva -- n -- 4. Who are behavioural public policy experts and how are they organised globally? - Holger Straßheim -- 5. Why nudge sometimes fails: fatalism and the problem of behaviour change - Tom Entwistle -- 6. Behavioural insights teams in practice: nudge missions and methods on trial - Sarah Ball and Brian W. Head -- 7. Can street-level bureaucrats be nudged to increase effectiveness in welfare policy? - Emilio Paolo Visintin, Jean-Michel Bonvin, Frédéric Varone, Fabrizio Butera, Max Lovey and Emilie Rosenstein -- 8. What motivates street-level bureaucrats to implement the reforms of elected politicians? - Don S. Lee and Soonae Park -- 9. How can better monitoring, reporting and evaluation standards advance behavioural public policy? - Sarah Cotterill, Peter John and Marie Johnston -- Conclusion - Benjamin Ewert, Kathrin Loer and Eva
Keywords: Political planning; Public administration -- Social aspects; Behaviorism -- (Political science); Verhaltensmodifikation; Nudge; Staatstätigkeit